Cross-cultural communication challenges among pedicab drivers and vendors with foreign tourists in Aceh, Indonesia - Dian Fajrina; Andri Wardana; Diana Achmad; Laily Nurul Adnin (Studies in English Language and Education, 2024)
In the context of globalization, English plays a pivotal role, particularly in the tourism industry, where daily interactions with foreign visitors are common. This study investigates the motivations, challenges, and efforts of pedicab drivers and vendors when communicating with foreign tourists at the Tsunami Museum and Ulee Lheue Port in Banda Aceh, Indonesia. Utilizing a qualitative descriptive approach, data were gathered through interviews with eight respondents: four pedicab drivers and four vendors. This studys findings reveal that pedicab drivers and vendors have a complex use of English, reflecting their motivations, challenges, and efforts to improve their language skills. The respondents expressed a strong desire to engage with foreign tourists, promote their products, and conduct tours, often motivated by positive interactions. However, they faced significant challenges, such as word recall, understanding foreign accents, and unfamiliar vocabulary, often relying on basic English or Indonesian for communication. To address these issues, they are making efforts to enhance their English proficiency through interactions with tourists and peers, demonstrating a commitment to improving communication and better serving their customers. The study emphasizes the need for improved language support in the tourism sector and offers valuable insights for educators. It accentuates the importance of increasing students awareness of Englishs practical relevance, especially for those pursuing careers in tourism and other globalized fields.